Genetic prognostication in uveal melanoma. Issue 4 (4th November 2017) - Dogrusöz, Mehmet; Jager, Martine J.
Abstract: Uveal melanoma (UM) is a rare tumour with a high propensity to metastasize. Although no effective treatment for metastases yet exists, prognostication in UM is relevant for patient counselling, planning of follow‐up and stratification in clinical trials. Besides conventional clinicopathologic characteristics, genetic tumour features with prognostic significance have been identified. Non‐random chromosome aberrations such as monosomy 3 and gain of chromosome 8q are strongly correlated with metastatic risk, while gain of chromosome 6p indicates a low risk. Recently, mutations in genes such as BAP1, SF3B1 and EIF1AX have been shown to be related to patient outcome. Genetics of UM is a rapidly advancing field, which not only contributes to the understanding of the pathogenesis of this cancer, but also results in further refinement of prognostication. Concomitantly, advances have been made in the use of genetic tests. New methods for genetic typing of UM have been developed. Despite the considerable progress made recently, many questions remain, such as those relating to the reliability of prognostic genetic tests, and the use of biopsied or previously irradiated tumour tissue for prognostication by genetic testing. In this article, we review genetic prognostic indicators in UM, also comparing available genetic tests, addressing the clinical application of genetic prognostication and discussing future perspectives for improving genetic prognostication in UM.